Incidence of hospital mortality in polytrauma patients in a tertiary center in Bosnia and Herzegovina - Hadžan Konjo; Emira Švraka; Đemil Omervić; Dijana Avdić (Journal of Health Sciences, 2016)
Introduction: In the late 70s of the last century, the mortality rate due to polytrauma amounted to 40%. This led to a new approach to this patient category with the goal of improving the treatment outcome.  According to the German trauma register, the rate of mortality in polytrauma at the end of the last century was 18.6%. The goal of this study is to determine the incidence of hospital mortality in polytrauma patients in a tertiary institution in Bosnia and Herzegovina.